Polypharmacy for the treatment of epilepsy in public health-care: an integrative literature review (Research, Society and Development, 2022)
Introduction: Epilepsy is a chronic alteration with modifications in brain functions, which can lead to loss of consciousness and presents partial or focal epileptic seizures. There are different etiologies for epilepsy, characterizing a varied treatment according to the particularity of the individual, which accentuates polypharmacy. Objective: To evaluate polypharmacy related to the treatment of epilepsy in the Brazilian public network, recognizing the exacerbated or inappropriate use of medications. Methodology: This is an integrative literature review conducted between the months of April and June 2022 in the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL), Virtual Health Library (VHL), and EBSCO Information Services. Results and discussion: About 50% of patients with epilepsy consume multiple medications, which increases morbidity and mortality due to the risks of adverse effects and the ability to increase seizures.  Epilepsy leads to autointoxication as a consequence of polypharmacy, especially in the elderly, due to pharmacological interactions, which must be monitored by doctors. The Brazilian Unified Health System has pharmaceutical assistance that promotes the rational use of drugs, seeking to select and standardize the drugs that are indicated and made available. Final considerations: Epileptic patients using polypharmacy tend to develop problems that hinder psychosocial performance and present a higher risk of adverse effects due to pharmacological interactions. Therefore, rational pharmacological use by balancing benefits and disadvantages becomes necessary.